2001
DOI: 10.1046/j.1469-8137.2001.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling ozone effects from seedlings to forest trees

Abstract: Biospheric ozone has become a widely distributed air pollutant, and a growing body of research indicates that ozone impacts forest health and productivity. Ozone effects are mediated by the ozone concentration present in the external environment and the movement of ozone into the leaf via the stoma. The cumulative dose received by the plant is, in the simplest terms, a function of ambient ozone concentration and stomatal conductance to water vapor. This relationship is important in understanding ozone flux int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 136 publications
(192 reference statements)
3
57
0
2
Order By: Relevance
“…This presents large challenges when scaling impacts beyond the tree level (Samuelson and Kelly, 2001). Earlier, Grünhage and Jäger (1994) suggested that O 3 flux into the plant could be used as an underlying mechanism for establishing standards to protect vegetation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This presents large challenges when scaling impacts beyond the tree level (Samuelson and Kelly, 2001). Earlier, Grünhage and Jäger (1994) suggested that O 3 flux into the plant could be used as an underlying mechanism for establishing standards to protect vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Building on their approach, we used indicator and response data recently available from a long-term, ecosystem-scale free-air manipulative experiment in which air quality and meteorological measurements were coupled in time and space against a backdrop of inter-annual variability in climate (Kubiske et al, 2006). To partly address some of the scaling challenges enunciated by Samuelson and Kelly (2001) and to advance forest O 3 risk analysis within the North American ambient air quality context, our initial exposureeresponse regression analysis was completed using models comprising key meteorological indicators (GDD, WS, PAR, RH, precip.) of O 3 concentration and one important O 3 flux regulator (SMC) that would have been expected to yield a first-order approximation of atmospheric O 3 flux and stomatal uptake, as originally proposed by Krupa et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the results from studies on frost hardening of conifer seedlings using a similar freeze-test technique to study II, have correlated fairly well with survival test results from field experiments on mature trees (Andersson 1992). In the case of exposure to O 3 , the response of mature trees to O 3 stress may differ from that of seedlings (Samuelson and Kelly 2001).…”
Section: Growth Of Young Aspen Under Variable Water and N Supplies Anmentioning
confidence: 99%
“…O O 3 entra nas folhas por meio dos estômatos e, no espaço intercelular, reage com a água formando espécies ativas de oxigênio (EAO), que têm um alto potencial oxidativo (Samuelson & Kelly 2001, Fuhrer & Booker 2003, Baier et al 2005. Entre estas espécies, encontram-se o radical superóxido (O 2˙-), o peróxido de hidrogênio (H 2 O 2 ), o radical hidroxila (OH˙) (Scandalios 1993) e o radical peridroxila (O 2 H˙) (Bray et al 2000).…”
Section: Introductionunclassified